2020
DOI: 10.1038/s41598-020-74046-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection by remote ischemic conditioning in the setting of acute ischemic stroke: a preclinical two-centre study

Abstract: Reperfusion is the only existing strategy for patients with acute ischemic stroke, however it causes further brain damage itself. A feasible therapy targeting reperfusion injury is remote ischemic conditioning (RIC). This was a two-centre, randomized, blinded international study, using translational imaging endpoints, aimed to examine the neuroprotective effects of RIC in ischemic stroke model. 80 male rats underwent 90-min middle cerebral artery occlusion. RIC consisted of 4 × 5 min cycles of left hind limb i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…Despite strong pre-clinical evidence of the effectiveness of RIC in protecting the heart and the brain against ischaemia/reperfusion injury, it has failed to translate into a clinical treatment of myocardial infarction or stroke. Studies conducted in young and healthy experimental animals reported that RIC can markedly reduce cortical infarcts [10,72,84]. Yet, clinical data show no major beneficial effect of RIC on stroke outcomes [68], although with some suggestion of reduced recurrent strokes with intracerebral artery stenosis treatment, and decreased stroke severity with carotid stenosis [69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite strong pre-clinical evidence of the effectiveness of RIC in protecting the heart and the brain against ischaemia/reperfusion injury, it has failed to translate into a clinical treatment of myocardial infarction or stroke. Studies conducted in young and healthy experimental animals reported that RIC can markedly reduce cortical infarcts [10,72,84]. Yet, clinical data show no major beneficial effect of RIC on stroke outcomes [68], although with some suggestion of reduced recurrent strokes with intracerebral artery stenosis treatment, and decreased stroke severity with carotid stenosis [69].…”
Section: Discussionmentioning
confidence: 99%
“…The animals were randomized into four experimental groups: (1) rats with MCAO/sham-RIC; (2) rats subjected to RIC starting 10 min before the onset of reperfusion; RIC protocol involved 4 cycles of 5 min left hind limb ischaemia interleaved with 5-min reperfusion periods [10,29], applied using an inflatable 12-mm cuff (IVM, USA). The cuff was inflated to 200 mmHg to stop the blood flow through the limb, as reported previously [12]; (3) rats with MCAO treated with a competitive GLP-1R antagonist Exendin (9-39) (Ex9, 50 μg kg −1 , intravenously) 20 min before the onset of reperfusion; (4) rats subjected to the RIC protocol starting 10 min before the onset of reperfusion and treated with Ex9 10 min prior to the first episode of RIC.…”
Section: Models Of Ischaemic Stroke and Remote Ischaemic Conditioning In Ratsmentioning
confidence: 99%
“…Marlene Wiart et al shared data from another preclinical stroke trial in rats that evaluated the neuroprotective effects of remote ischemic conditioning [11]. The primary endpoint was edema-corrected lesion size measured by T2-weighted MRI at 24 h of reperfusion normalized by the area-at-risk of infarction determined from per-occlusion MRI for each individual.…”
Section: Contributions Of Preclinical Mri To the 3rsmentioning
confidence: 99%
“…Exclusion rates are rarely reported in stroke research, which actually represents one of the methodological flaw of preclinical studies. Basalay et al recently reported a 25% exclusion rate at 24h post-surgery due to the combination of mortality rate and hemorrhagic transformations in a bicentre international study using the same tMCAO model in rats (37). For long-term studies, the mortality rate is increased as seen in the current study, where the mortality post-surgery exceeded our a priori hypothesis: this is a further element to be taken into account when designing a therapeutic trial to reach the adequate statistical power.…”
Section: Discussionmentioning
confidence: 99%